ANALISIS PERUBAHAN KEMIRINGAN SUDUT ANTENA TERHADAP UNJUK KERJA PERANGKAT NANOSTATION2 LOCO (NS2L) PADA OUTDOOR HOTSPOT SYSTEM - Mishan . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2016)
Inclination is the angle formed by tilt angle to vertical line. This research determine the effect of tilt angle to the performance of the device, changes the quality, affordability and stability of connections. In addition, this research also presented the comparative performance of the device after tilt angle changed  and  find  the optimal angle. This research, explained  the change in  angle of inclination generally affected the main lobe and back lobe in the antenna’s beam of NanoStation2 Loco. Inclination angle also causes the signal strength and connection stability affected, especially on devices at distance over 100 m from the antenna. This research made changes three times to the antenna’s tilt. There are 10 °, 20 ° and 30 °. From the angle change, the result indicates that the most effective use of research sites of the Faculty of Engineering, University Tanjungpura Pontianak is tilted at angle of 20°. This is proved by results of measuring Received Signal Strength Indicator and Packet Loss that be the main indicator to determine the quality of the antenna. From the data showed the measurement of signal strength under -90 dBm at distance over 100 m will lead the connection and stability to be poor connection. This situation is shown by the high number percentage of packet loss that occurs during pingtest. At the point of measurement locations under 100 m and minimum obstacle, change angles do not have a big impact and quality of the antenna is in excellent. In addition to the distance from the antenna, the obstacle factors (barriers of the building) is also a big influence on the quality of the antenna.